Who’s Who at the Border? A rights-based approach to identifying human trafficking at international borders - McAdam, Marika (Anti-Trafficking Review, 2013)
International borders are widely touted as bastions in the fight against trafficking in persons. This article acknowledges the important role border officials play in preventing human trafficking, but calls for expectations to be tempered by deference to the conceptual complexity of cross-border trafficking and the migration processes involved. The fact that many trafficked victims begin their journeys as irregular or smuggled migrants highlights the challenge posed to border officials in identifying trafficked persons among the people they encounter. Indicators of trafficking generally relate to the exploitation phase, leaving border officials with little guidance as to how persons vulnerable to trafficking can be accurately identified before any exploitation has occurred. Ultimately, this paper advocates a pragmatic rights-based approach in designating anti-trafficking functions to border officials. A rights-based approach to border control acknowledges the core work of border officials as being to uphold border integrity, while ensuring that their performance of this role does not jeopardise the rights of those they intercept nor result in missed opportunities for specialists to identify trafficked persons and other vulnerable people among them.